Living Qur’an di Pondok Pesantren Hamalatul Qur’an Syifa Warohmah Dagangan Madiun - Sofyan Ghufronul Uzka (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2024)
This study discusses the Living Qur'an phenomenon that occurs in the community, such as the tradition of reading Surah Al-Fatá¸¥ verse 29 at the Syifa Warohmah Dagangan Madiun Islamic Islamic Boarding School Hamalatul Qur'an. This activity was attended by all students and administrators which was carried out every night after the Isha prayer. This type of research is descriptive qualitative. Data collection techniques using the methods of observation, interviews, and documentation. The focus of the discussion of this research is on how to practice and what are the motives, goals, and meanings of the tradition of reading Surah Al-Fatá¸¥ verse 29 at the Syifa Warohmah Dagangan Islamic Boarding School in Madiun based on the phenomenological theory of Alferd Schutz. The results of the research in this thesis indicate that the tradition of reading Surah Al-Fatá¸¥ verse 29 at the Syifa Warohmah Dagangan Islamic Boarding School in Madiun was carried out after the Isha' prayer and the hajat prayer, then one of the students took the rice that was in the container (plate) and distributed to the administrators and other students, amounting to five seeds for each person, while accompanied by three times shalawat Nariyah. Then every single grain of rice is recited Surah Al-Fatá¸¥ verse 29 and then blown, repeated five times. After the procession is complete, the rice is returned to its container. Closed with Shalawat Burdah. The motive for the students and administrators to participate in this activity is due to the rules of the lodge and routine activities every night. The goal is to facilitate sustenance, expect blessings, and increase memorization. There are two meanings, the objective meaning is as the practice of facilitating sustenance, the subjective meaning is a form of gratitude, ijasahan, blessing.